2008
DOI: 10.1007/s10886-008-9573-5
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Signals During Pregnancy: A Possible Chemical Basis for Mother–Infant Recognition

Abstract: Publisher's copyright statement:The nal publication is available at Springer via http://dx.doi.org/10.1007/s10886-008-9573-5. Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…The observation that pregnancy alters scent profiles in lemurs (this study) and in humans [11] suggests that olfactory cues of pregnancy may be widespread or highly conserved among primates. Such findings highlight the importance of considering multiple sensory modalities when examining reproductive signals, even in taxa historically thought to rely relatively little on olfaction [7,30,31].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The observation that pregnancy alters scent profiles in lemurs (this study) and in humans [11] suggests that olfactory cues of pregnancy may be widespread or highly conserved among primates. Such findings highlight the importance of considering multiple sensory modalities when examining reproductive signals, even in taxa historically thought to rely relatively little on olfaction [7,30,31].…”
Section: Discussionmentioning
confidence: 55%
“…Given the established link between sex steroids and olfactory profiles [7], these findings suggest possible endocrine involvement (or competing energy allocation) in the production of olfactory gestational cues. Gestational cues could serve various functions across primate species, from promoting social cohesion [3] to engendering parental investment [4] or kin recognition [11]. To the extent that olfactory cues of pregnancy occur in other primates, our findings could be relevant to these existing hypotheses, as well as to theories on the functionality of multiple mating.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…If we interpret the results at face value, it may be that recognition of mother's smells in infanthood is possible because her odour is more distinctive around the perinatal period. According to Vaglio (2009), mothers develop a distinctive pattern of 5 volatile compounds common to the nipple-areola and para-axillary regions in late pregnancy and early post-partum, and perhaps these odour changes shape their distinctiveness. In addition, it is possible that the benefits of recognition are simply more important when at this time, since babies must find the breast for nourishment, compared to post-weaning, and perhaps because they rely more on olfaction than vision at this time of their development.…”
Section: Discussionmentioning
confidence: 99%
“…Vaglio et al (20) confirmed that during pregnancy, and immediately after delivery, women develop a particular chemical profile of volatile molecules that are different from the profile of women who have not given birth and from women who are caring for infants they did not give birth to. In particular, five specific different volatile molecules -1-dodecanol, 1-1 0 -octane Oxybis, isocurcumenol, ð-hexylcinnamic, aldehyde and isopropyl mystrate -have been identified in samples collected from the area of the nipple, the areola and the axilla of pregnant women and women after childbirth.…”
Section: Discussionmentioning
confidence: 99%